Program CSR Berbasis Pemberdayaan Masyarakat Menuju Kemandirian Ekonomi Pasca Tambang di Desa Sarĳaya - Asa Ria Pranoto; Dede Yusuf (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
Corporate Social Responsibility (CSR), is the company’s commitment to contribute to sustainable economic development by taking into account the social aspects and the environment. PT Pertamina EP as one of the major industrial companies operating internationally and has a fundamental problem in the implementation of their CSR, namely how the planning and implementation of the CSR program, as well as through any indicator PT Pertamina EP is able to apply a good CSR refers to the MDGs documents, regulations regulations and ISO 26000. this study aimed to measure the eﬃ ciency of the implementation as well as the response and participation in the implementation of CSR programs conducted.